Translating Global Environmental Constitutionalism in the Indonesian Context: Pancasila vs. Liberalism - Mustolikh, Amran (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
The translation of global environmental constitutionalism into local contexts presents a complex interplay between universal principles and indigenous values. This paper investigates this dynamic within the Indonesian context, juxtaposing the principles of Pancasila, the state ideology, with liberal environmental constitutionalism. While global environmental constitutionalism emphasizes individual rights, liberal democracy, and market mechanisms, Pancasila is rooted in collective welfare, harmony, and indigenous cultural values. The analysis begins by delineating the core tenets of liberal environmental constitutionalism, highlighting its focus on individual rights to environmental protection and the centrality of democratic governance. It then contrasts these principles with the philosophical underpinnings of Pancasila, which prioritize collective well-being, socio-cultural harmony, and state intervention for sustainable development. Furthermore, the paper examines the implications of translating liberal environmental constitutionalism into the Indonesian context. It identifies potential points of convergence and divergence between liberal ideals and Pancasila-based governance structures. Challenges such as reconciling individual rights with collective welfare, integrating indigenous knowledge into environmental policymaking, and navigating the tensions between state intervention and market mechanisms are discussed. Through this analysis, the paper contributes to the ongoing discourse on global environmental constitutionalism by emphasizing the importance of contextual adaptation. It underscores the need for flexible frameworks that accommodate diverse cultural, political, and economic realities. Ultimately, it argues for a nuanced approach that recognizes the value of both universal principles and indigenous wisdom in shaping effective environmental governance systems within specific national contexts.